A new approach for modeling flux variation in membrane filtration and experimental verification. (1st December 2019) - Taghavijeloudar, Mohsen; Park, Junboum; Han, Mooyoung; Taghavi, Ali
Abstract: It is important to model flux variation during the membrane filtration process, particularly in the early stage of filtration where severe fouling causes rapid flux decay in a short period of time. The objective of this study was to develop a combined fouling mathematical model based on energy head loss principle for prediction of flux variation in the membrane filtration. The complete-cake model was employed in the model in order to describe the loss of membrane available area due to pore clogging, while, the classical cake model was used for cake filtration. A new dimensionless parameter, namely the filter number (FN) was proposed in this study to account for the unmeasurable properties of the membrane in the model. The application of the proposed model was tested and compared with the existing models using experimental data for the filtration of wastewater sludge, microalgae suspension and sodium alginate solution with different membranes and pressures. The results showed that the flux calculated values of the new model had good agreements with the experimental data under different conditions. According to statistical analyses, the model improved the representing accuracy of flux variation in the early stage of filtration. In addition, the model provides better performance and efficiency in comparison to the existing models for high flux operations which is more conventionally applied in the industry and is expected to be more in the future. Graphical abstract: Image 1 Highlights: A mathematical model for flux variation in membrane filtration has been developed. Membrane pore blocking was characterized using a new dimensionless factor. The model was tested against three suspensions of deformable, non-ideal particles. The model gives a better fit to the data in comparison to the existing models. The model well described flux rapid decay in the early stage of filtration.